Creativity in Hospitality Industry: Study of Hostels in St. Petersburg - Irina Borovskaya (Santalka: Filosofija, Komunikacija, 2014)
The aim of this study is to explore dimensions of creativity in hostels managerial practices taking the example of St. Petersburg. Within the study 72 semi-structured interviews were conducted with owners and employees of hostels during October–November 2012. The findings of the study identify four main managerial activities as key elements of creativity in hostels. They are: targeted recruitment, segmentation of customers, organization of space, and organization of communications both with internal and external stakeholders.